Intra-alveolar auto-transplantation to correct a single tooth rotation: A case report with four years of follow-up - Sunil Babu Kotha (Wolters Kluwer Medknow Publications, 2014)
It is uncommon for children or young adults to have rotated central incisors. The restorative options are to carry out an orthodontic treatment or root canal treatment followed by crown placement for their correction. Often overlooked and misunderstood, another treatment option in the intra-alveolar auto-transplantation where the tooth is rotated within the same socket to an appropriate position. This article highlights the overview of intra-alveolar auto-transplantation along with a case of rotated central incisor. A 12-year-old complaining of rotated tooth and wanted it to be corrected. On clinical examination, there was rotation of maxillary left central incisor with no history of any gingival and periodontal involvement. After obtaining the consent from the patient and his parent, intra-alveolar auto-transplantation procedure was carried out. After a four-year follow-up, the concerned tooth, had retained its vitality and showed no signs of relapse.